Prostate Biopsy Sampling Causes Hematogenous Dissemination of Epithelial Cellular Material. (28th January 2014) - Ladjevardi, Sam; Auer, Gert; Castro, Juan; Ericsson, Christer; Zetterberg, Anders; Häggman, Michael; Wiksell, Hans; Jorulf, Håkan
Abstract : The extent of epithelial cellular material (ECM) occurring in venous blood samples after diagnostic core needle biopsy (CNB) was studied in 23 patients with CNB diagnosed prostate cancer without provable metastases and 15 patients without cancer. The data show a significant increase of ECM in the peripheral blood sampled 20 seconds or 30 minutes after the last of 10 CNB procedures compared to the number of ECM detectable in the blood samples taken before the performance of CNB. The data indicate that diagnostic CNB of prostate cancer causes an extensive tissue trauma with a potential risk of cancer cell dissemination.